Changes in circulating stem cells and endothelial progenitor cells over a 12-month period after implantation of a continuous-flow left ventricular assist device - Ivak, Peter; Netuka, Ivan; Kralova-Lesna, Ivana; Wohlfahrt, Peter; Pitha, Jan (Archives of medical science, 2020)
INTRODUCTION: Changes in circulating CD34+CD45low stem cells (SC) and CD34+CD45low+KDR+ endothelial progenitor cells (EPC) may reflect pathological endothelial activation. Non-pulsatile/continuous-flow left ventricular assist devices (CF-LVAD) can enhance this process. The aim of this study was to analyse the impact of 12-month CF-LVAD treatment on SC and EPC. METHODS: We analysed changes in SC and EPC from the pre-implantation period up until 12 months after implantation over 3-month intervals in 14 patients. Data from 12 patients with heart failure (HF) and from 13 healthy volunteers were used as controls. RESULTS: Baseline EPC were significantly higher in CF-LVAD and HF patients than in healthy controls, substantially decreasing 3 months after CF-LVAD implantation and then returning to high baseline values at 12 months. CONCLUSIONS: Changes in circulating SC and EPC may reflect pathological endothelial activation after CF-LVAD implantation.
Keywords: mechanical circulatory support; endothelial progenitor cells; continuous flow; stem cells; endothelial damage